Georgian and Victorian board games the Liman Collection - Slesin, Suzanne (Pointed Leaf Press, 2017)
As the turn from the 18th to the 19th century approached in Great Britain, more and more parents and teachers embraced a suggestion from the philosopher John Locke that learning might be made a play and recreation to children. 'Georgian and Victorian Board Games: The Liman Collection' includes the most beautiful and rare games of the time collected by Arthur Liman. Showcasing 50 games that were made for both instruction and delight, the book reflects on a transatlantic market that flourished into and through the 19th century. Although games were often printed on linen or board instead of delicate paper, many fell apart due to enthusiastic use. But those that survived open a window onto the time period in which they were created, reflecting its social and moral priorities as well as a wide range of educational subjects. 'Georgian and Victorian Board Games: The Liman Collection' will appeal to both experts and people who will discover this unusual art form for the first time. The oversize format allows for a close inspection and reading of the wonderfully imaginative and interesting information on the museum-quality game boards while reproductions of some of the pages from the detailed instruction booklets allow for an even deeper look into the games and how they were played. The games themselves are beautifully detailed?produced by a handful of the best-known publishers of the era, the hand-color engraved games look as vibrant and colorful as they did two centuries ago. Also included in the lavishly produced book are five gatefolds that illustrate the games and their complete instructions and rules so as to allow modern readers to try their hand at these fascinating and historic games
Keywords: Geschichte 1740-1900; Brettspiel; Großbritannien; Board games; Katalog